2022
DOI: 10.5603/cj.a2021.0174
|View full text |Cite
|
Sign up to set email alerts
|

The Klotho protein supports redox balance and metabolic functions of cardiomyocytes during ischemia/reperfusion injury

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
1
7
0
1
Order By: Relevance
“…In our previous research, we showed that Klotho improved the viability and metabolic activity of the cardiomyocytes during IRI, and was proposed as a biomarker of heart damage [ 16 ]. We then showed a supported redox balance by means of Klotho protein in injured cardiac cells [ 17 ]. For this reason, we hypothesized that through the reduction of oxidative stress, Klotho may break the cascade involved in IRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research, we showed that Klotho improved the viability and metabolic activity of the cardiomyocytes during IRI, and was proposed as a biomarker of heart damage [ 16 ]. We then showed a supported redox balance by means of Klotho protein in injured cardiac cells [ 17 ]. For this reason, we hypothesized that through the reduction of oxidative stress, Klotho may break the cascade involved in IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Our further studies showed that the administration of the nitric oxide synthase, MMP-2 and myosin light chain kinase inhibitors led to cardioprotection in the human cardiomyocytes or the isolated rat hearts [ 7 , 35 , 36 ]. We then proved that Klotho protein participates in the regulation of a redox balance and supports metabolic homeostasis of the cardiomyocytes [ 17 ]. In the current research, increased injury in the cells subjected to IRI was shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuregulin-1 attenuates oxidative stress and inflammation by inhibiting Nox4 and NLR family pyrin domain containing 3 (NLRP3)/caspase-1 in myocardial I/R injury [ 56 ]. Klotho, an anti-aging single-pass membrane protein, decreases Nox2 and Nox4 levels in cardiomyocytes during I/R [ 57 ]. These upstream regulators of Nox2 and Nox4 are potential targets for the treatment of myocardial I/R injury.…”
Section: Novel Regulatory Mechanisms Of Nox and Its Crosstalk With Ot...mentioning
confidence: 99%
“…Кардиомиоциты человека подверглись химическому И/Р-повреждению in vitro (с цианистым натрием и 2-дезоксиглюкозой) в присутствии или в отсутствие Re-KL. Введение белка Klotho привело к уменьшению повреждения, снижению уровня NOX2 и NOX4, уменьшению образования АФК, активных форм азота и H 2 O 2 , снижению экспрессии индуцируемой NOS и ограничению продукции нитратов/нитритов в клетках при ишемии/реперфузии [68].…”
Section: роль белка Klotho при атеросклерозе и связанных с ним заболе...unclassified